2000
DOI: 10.1523/jneurosci.20-20-j0003.2000
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5-Triphosphate-Evoked Responses in Midbrain Dopamine Neurons

Abstract: Synaptically released glutamate evokes slow IPSPs mediated by metabotropic glutamate receptors (mGluRs) in midbrain dopamine neurons. These mGluR IPSPs are caused by release of Ca(2+) from intracellular stores and subsequent activation of small-conductance Ca(2+)-activated K(+) channels (SK channels). To further investigate the intracellular mechanisms involved, the effect of photolyzing intracellular caged inositol 1,4,5-triphosphate (InsP(3)) on membrane conductance and intracellular Ca(2+) concentration ([C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 24 publications
(28 reference statements)
8
55
0
Order By: Relevance
“…In addition, the lack of effect of MPEP indicates that mGluR5 is not involved, which is consistent with the expression of the mGluR1 subtype in DA cells (Testa et al, 1994;Kosinski et al, 1998). Interestingly, it has been reported that tetanic stimulation of excitatory fibers induces slow mGluR1-mediated excitatory and inhibitory responses (Shen and Johnson, 1997;Fiorillo and Williams, 1998) accompanied by rapid increases in intracellular Ca 2ϩ attributable to mobilization from the intracellular stores (Fiorillo and Williams, 1998;Guatteo et al, 1999;Morikawa et al, 2000). Thus, it might be speculated that rises in intracellular Ca 2ϩ leading to endocannabinoid synthesis and release might result from activation of intracellular pathways downstream of the activation of mGluR1.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, the lack of effect of MPEP indicates that mGluR5 is not involved, which is consistent with the expression of the mGluR1 subtype in DA cells (Testa et al, 1994;Kosinski et al, 1998). Interestingly, it has been reported that tetanic stimulation of excitatory fibers induces slow mGluR1-mediated excitatory and inhibitory responses (Shen and Johnson, 1997;Fiorillo and Williams, 1998) accompanied by rapid increases in intracellular Ca 2ϩ attributable to mobilization from the intracellular stores (Fiorillo and Williams, 1998;Guatteo et al, 1999;Morikawa et al, 2000). Thus, it might be speculated that rises in intracellular Ca 2ϩ leading to endocannabinoid synthesis and release might result from activation of intracellular pathways downstream of the activation of mGluR1.…”
Section: Discussionsupporting
confidence: 64%
“…The peak of the IP 3 -evoked outward current (I IP3 ) trace was not rounded even with a supramaximal intensity of UV pulse, suggesting that SK channels were not saturated by Ca 2ϩ . Our previous study also demonstrated approximately linear relationship between the I IP3 amplitude and [Ca 2ϩ ] i over a wide range in DA neurons (Morikawa et al, 2000). The amplitude of I IP3 elicited with a supramaximal UV intensity was 350 -700 pA (515 Ϯ 37 pA; n ϭ 10).…”
Section: Methodssupporting
confidence: 52%
“…It should also be noted that DHPG-induced inhibition of I mGluR slowly recovered over a period of ϳ10 min after washout of DHPG, likely reflecting slow replenishment of Ca 2ϩ stores (Solovyova and Verkhratsky, 2003). It has been shown that IP 3 Rs and RyRs are expressed on a common pool of Ca 2ϩ stores in DA neurons (Morikawa et al, 2000). Recent evidence further suggests that the endoplasmic reticulum in DA neurons may actually be a single, interconnected lumen (Choi et al, 2006).…”
Section: Ip 3 Mediates Differential Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In several types of neurons, however, elevation of intracellular Ca 2+ has been shown to activate Ca 2+ -activated K + channels, thereby producing a long-lasting after-hyperpolarization of an action potential to reduce neurotransmitter release from synaptic terminals (Cassell and McLachlan, 1987;Kawai and Watanabe, 1989;Marrion and Tavalin, 1998). The IP 3 -evoked activation of Ca 2+ -activated K + channels plays a role in regulating the excitability of rat midbrain dopamine neurons (Morikawa et al, 2000). Furthermore, ryanodine receptors have been shown to form a functional triad with Ca 2+ -activated K + channels and voltage-gated Ca 2+ channels located on the cell membrane, thereby directly shaping the spike repolarization of an action potential in bullfrog sympathetic neurons (Akita and Kuba, 2000).…”
Section: Cytosolic Camentioning
confidence: 99%